A Quasi-experimental Study to Assess the Effectiveness of Reminiscence Therapy on Depression among Hospitalized Elderly Undergoing Abdominal Surgery Admitted in Nehru Hospital, PGIMER, Chandigarh - Ritika Tandon; Rajesh Gupta; Sunita Sharma; Mukta Thakur (Indian Journal of Psychiatric Nursing)
Background: Improved health-care quality has led to a global increase in the elderly population. With the increase in life expectancy, the number of elderly patients with surgically correctable diseases has also increased. Abdominal operations are common among the elderly due to the increased incidence of gastrointestinal tract disorders. It is not uncommon for older adults who are undergoing abdominal surgery to experience depression during their hospital stay. Reminiscence therapy is one of the most widely used interventions to alleviate depressive feelings among older adults. Being aware of this risk and providing therapeutic intervention such as reminiscence therapy is crucial to ensure patients make a full and successful recovery. Objective: The objective of the study was to assess the level of depression among the elderly undergoing abdominal surgery and to assess the effectiveness of reminiscence therapy on depression among hospitalized elderly undergoing abdominal surgery admitted in Nehru Hospital, PGIMER, Chandigarh. Materials and Methods: A quasi-experimental study was conducted in the surgical unit of Nehru Hospital at PGIMER, Chandigarh. The institute ethics committee granted ethical approval for the project with the reference number INC/IEC/2021/SPL.1146. The approval was issued on July 28, 2021. Written consent was obtained from all 60 participants who were selected using a purposeful sampling approach. Randomization was done through an alternate allocation method, assigning each group of 30 participants to both the experimental and control groups. Data were collected from patients through interviews conducted between July 2021 and September 2021. The interviews covered their sociodemographic background, clinical profile, and geriatric depression scale scores. Reminiscence therapy was only provided to the experimental group, which underwent four sessions lasting 45–60 min. The control group had no intervention. Results: After undergoing reminiscence therapy, subjects in the experimental group exhibited a significant reduction in depression levels. About 83.4% of the subjects had no depression, while 16.6% had mild depression. No change was observed in the control group. There was a significant decrease in depression scores in postassessment in the experiment group, P value (<0.001) as compared to the control group. Conclusion: Reminiscence therapy appeared to be successful in reducing depression in hospitalized elderly patients undergoing abdominal surgery. The use of nonpharmacological methods, such as reminiscence therapy, can be a cost-effective way to manage depression.